2020
DOI: 10.1101/2020.04.18.047738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional Genome Organization Maps in Normal Haematopoietic Stem Cells and Acute Myeloid Leukemia

Abstract: Acute Myeloid Leukemia (AML) is a highly lethal blood cancer arising due to aberrant differentiation of haematopoietic stem cells. MEIS1 and HOXA9 regulate stemness-related transcriptional programs in normal haematopoietic stem cells and AML. Here we obtained 3D genome organization maps in the CD34+ haematopoietic stem cells from 3 healthy individuals and 3 individuals with AML. The MEIS1 oncogenic transcription factor is regulated by a Frequently Interacting Region (FIRE). This FIRE is present in normal bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Loop calls from in-situ Hi-C experiments on HAP1 cells were obtained from [40]. Loop and TAD calls from in-situ Hi-C experiments on HSC samples were obtained from [45]. Loop calls from additional Hi-C experiments on HSC samples were obtained from [46].…”
Section: Methodsmentioning
confidence: 99%
“…Loop calls from in-situ Hi-C experiments on HAP1 cells were obtained from [40]. Loop and TAD calls from in-situ Hi-C experiments on HSC samples were obtained from [45]. Loop calls from additional Hi-C experiments on HSC samples were obtained from [46].…”
Section: Methodsmentioning
confidence: 99%
“…Loop and TAD calls from in-situ Hi-C experiments on HSC samples were obtained from ref. 51 . Loop calls from additional Hi-C experiments on HSC samples were obtained from ref.…”
Section: Dataset Geo Accession Numbersmentioning
confidence: 99%
“…generated in this study have been deposited in the Gene Expression Omnibus (GEO) database under accession code GSE222526. Publicly available sequencing datasets analyzed in this study include loop data that can be found in the supplementary information of 51 . H3K4me2 ChIA-PET can be accessed from GSE32677.…”
Section: Atac-seq Experimentsmentioning
confidence: 99%